2023
DOI: 10.1021/acs.est.3c04192
|View full text |Cite
|
Sign up to set email alerts
|

Continuous NO Upcycling into Ammonia Promoted by SO2 in Flue Gas: Poison Can Be a Gift

Abstract: Although ammonia (NH3) synthesis efficiency from the NO reduction reaction (NORR) is significantly promoted in recent years, one should note that NO is one of the major air pollutants in the flue gas. The limited NO conversion ratio is still the key challenge for the sustainable development of the NORR route, which potentially contributes more to contaminant emissions rather than its upcycling. Herein, we provide a simple but effective approach for continuous NO reduction into NH3, promoted by coexisting SO2 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Thus, it was clearly found that the MnOOH cocatalyst is located on the BiVO 4 /Cu 2 O S-scheme heterojunction. 39…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it was clearly found that the MnOOH cocatalyst is located on the BiVO 4 /Cu 2 O S-scheme heterojunction. 39…”
Section: Resultsmentioning
confidence: 99%
“…The chemical redox pair of SO 2 -Fe(III) is illustrated in eqn ( 21)- (23). 114 Fe(II) / Fe(III) (spontaneous oxidation) (21)…”
Section: No X Upcycling To Ammoniamentioning
confidence: 99%
“…Furthermore, the on-site coupled system demonstrated the synergistic removal and recycling of NO and SO 2 without the need for scavengers. 114 The formation of the SO 2 –NO redox pair facilitates high conversion rates of both NO and SO 2 in continuous flow. Achieving a remarkable selectivity for both NO-to-NH 3 upcycling (97%) and SO 2 -to-SO 4 2− purification (92%) simultaneously underscores the practicability of value-added conversion of air pollutants ( Fig.…”
Section: No X Upcycling To Ammoniamentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9] Notably, the combustion of fossil fuels and emissions from vehicle exhaust have significantly increased the concentration of nitric oxide (NO) in the atmosphere. [10][11][12] This rapid rise in NO level has severely impacted the environment (e.g., photochemical smog, ozone layer depletion, and acid rain) and human health. [13,14] Currently, the predominant method for NO removal is selective catalytic reduction (SCR) technology, which typically requires the utilization of valuable reducing agents such as ammonia (NH 3 ) or urea.…”
Section: Introductionmentioning
confidence: 99%